2015
DOI: 10.1099/jmm.0.000150
|View full text |Cite
|
Sign up to set email alerts
|

Inactivating effects of the lactoperoxidase system on bacterial lyases involved in oral malodour production

Abstract: The main components of oral malodour have been identified as volatile sulfur compounds (VSCs), including hydrogen sulfide (H 2 S) and methyl mercaptan (CH 3 SH). The lactoperoxidase (LPO) system (consisting of LPO, glucose oxidase, glucose and thiocyanate) was previously shown to exhibit antimicrobial activities against some oral bacteria in vitro and suppressive effects on VSCs in mouth air in a clinical trial. Here, we examined the in vitro effects of the LPO system on the activities of the bacterial lyases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…28 LF + LPO tablets had an inhibitory effect on halitosis within a short period of time in healthy adults, 11 with the LPO system suppressing the production of VSC using its antimicrobial effects and inactivation of the bacterial lyases of F. nucleatum and P. gingivalis. 29 As we were unable to control the food and drinks consumed by the participants of the present study, the VSC component gas concentration at baseline was low and did not allow evaluation of the influence of the intervention on oral malodor.…”
Section: Discussionmentioning
confidence: 84%
“…28 LF + LPO tablets had an inhibitory effect on halitosis within a short period of time in healthy adults, 11 with the LPO system suppressing the production of VSC using its antimicrobial effects and inactivation of the bacterial lyases of F. nucleatum and P. gingivalis. 29 As we were unable to control the food and drinks consumed by the participants of the present study, the VSC component gas concentration at baseline was low and did not allow evaluation of the influence of the intervention on oral malodor.…”
Section: Discussionmentioning
confidence: 84%
“…Lactoferrin has antibacterial, anti‐biofilm, and anti‐inflammatory activity . The LPO system exhibits a bactericidal effect against pathogens, and LPO itself shows an anti‐inflammatory effect . During the dissolution of LF and LPO‐containing tablets in the mouth, the salivary concentrations of LF and LPO increase about 100‐ and 30‐fold compared with the basal state, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this moderate antibacterial effect, the suppressive effects of the active ingredients on VSCs were demonstrated in the present and previous studies. A recent in vitro study reported that the LPO system exhibited inactivation activity against the bacterial lyases related to the production of VSCs [ 21 ]. Inactivation activity may be the main contributor to suppressive effects on VSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous clinical trial that enrolled 15 healthy volunteers aged 26–54 years, sucking a trial tablet containing 100 mg of LF, 1.8 mg of LPO, and 24 mg of Sumizyme PGO which was composed of dextrin and GO, had short-term suppressive effects on the concentrations of VSCs in mouth air [ 20 ]. The underlying mechanisms of action reducing VSCs were suggested to involve the antimicrobial effects of LF and the LPO system [ 20 ] in addition to the inactivating effects of the LPO system on bacterial lyases involved in the production of VSCs [ 21 ]. Based on these findings, a powder composition including 20 mg of LF, 2.6 mg of LPO, and 2.6 mg of GO was developed for functional food products [ 22 ].…”
Section: Introductionmentioning
confidence: 99%